A budgeting crisis at Little State University - McEvoy, Chad D., 1971-; Gray, Dianna P. (London : Human Kinetics, Inc., 2012)
The Little State University Athletic Department faces an immediate budgeting crisis. Due to state budgeting woes, the legislature has reduced its allocation to Little State significantly for the upcoming year. The impact of this reduction included a loss of $800,000 to the athletic department, which represents approximately ten percent of the athletic budget. LSU Athletic Director Beth Duncan must determine how to best make the necessary cuts while preserving a strong department and minimizing the impact on student-athletes.
Originally published in McEvoy, C.D., & Gray, D.P. (2012). A Budgeting Crisis at Little State University. Case Studies in Sport Management 1(1), 10-17. DOI:.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Little State University. -- Athletic Dept; School budgets